2007
DOI: 10.1897/06-397r.1
|View full text |Cite
|
Sign up to set email alerts
|

Mixtures of metals and polynuclear aromatic hydrocarbons elicit complex, nonadditive toxicological interactions in meiobenthic copepods

Abstract: Abstract-The acute toxicity of metal-polynuclear aromatic hydrocarbon (PAH) mixtures (i.e., Cd, Hg, Pb, fluoranthene, and phenanthrene) associated with sediments was assessed in two benthic copepods. Schizopera knabeni was exposed to sediment amended with single contaminants and mixtures. Adult S. knabeni were highly tolerant of single-contaminant exposures to phenanthrene, Cd, Hg, and Pb as well as a mixture of Cd, Hg, and Pb. Binary experiments revealed that although phenanthrene was synergistic with Cd and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…On the other hand, Vellinger et al [40] observed an antagonist 'between-metals' interaction on Gammarus pulex exposed to binary mixtures of cadmium and arsenate. An antagonist effect between Cd, Hg, and Pb was also reported by Fleeger et al [41] on benthic copepods Schizopera knabeni.…”
Section: Resultssupporting
confidence: 74%
“…On the other hand, Vellinger et al [40] observed an antagonist 'between-metals' interaction on Gammarus pulex exposed to binary mixtures of cadmium and arsenate. An antagonist effect between Cd, Hg, and Pb was also reported by Fleeger et al [41] on benthic copepods Schizopera knabeni.…”
Section: Resultssupporting
confidence: 74%
“…In regions such as this, where site remediation is a priority and redevelopment is a likely future scenario, a thorough understanding of the spatial extent of contaminant-induced toxicity is necessary to guide management decisions. Absent an individual causative agent or clear understanding of multi-contaminant interactions, delineation of impacted regions based solely on chemical data is inadequate (Chapman 2002; Fleeger et al 2007; Kwok et al 2014; Pourabadehei and Mulligan 2016). The first objective of the present study was to demonstrate the usefulness of toxicity testing as a tool for delineating contaminant effects, particularly the unconventional use of toxicity tests on subsurface sediments from cores.…”
Section: Introductionmentioning
confidence: 99%
“…A. atopus is also more sensitive to cadmium (LC 50 96 h, 4.13 ± 0.75 μMol Cd; [63]) than to copper (LC 50 96 h, 4.42–6.23 μMol Cu), although the lower limit of the LC 50 of Cu overlaps with that of Cd. The lower sensitivity to copper relative to cadmium is the reverse to that observed for Tigriopus japonicus [64] and for Tisbe holothuriae [65].…”
Section: Resultsmentioning
confidence: 99%